2009
DOI: 10.1103/physrevb.79.033107
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency electron paramagnetic resonance of the hole-trapped antisite bismuth center in photorefractive bismuth sillenite crystals

Abstract: The hole-trapped antisite bismuth center has been directly observed by W-band ͑94 GHz͒ electron paramagnetic resonance ͑EPR͒ in the series of sillenite crystals, Bi 12 MO 20 ͑M = Ge, Si, Ti, denoted as BMO͒, either nondoped or doped with transition ions ͑Cr, Cu, Ru, Ce͒. Blue light illumination influences the EPR intensity in most crystals, while in nondoped Bi 12 GeO 20 and Bi 12 SiO 20 the signals only appear upon illumination. The spectra can be attributed to a single species and no anisotropy could be dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Electron paramagnetic resonance (EPR) measurements show that transition metal impurities often go into the tetrahedrally coordinated Ge site [17][18][19][20]. In this article, we present an investigation of the PL response of Bi 12 GeO 20 doped with the 4d ion Mo.…”
Section: Introductionmentioning
confidence: 97%
“…Electron paramagnetic resonance (EPR) measurements show that transition metal impurities often go into the tetrahedrally coordinated Ge site [17][18][19][20]. In this article, we present an investigation of the PL response of Bi 12 GeO 20 doped with the 4d ion Mo.…”
Section: Introductionmentioning
confidence: 97%
“…7,10 Also, the EPR spectrum of the antisite Bi M 4+ hole type defect is absent in BSO:Cr+P even after near-UV excitation, while we did observe it in a series of undoped and doped BMO crystals, 14 in particular in singly-doped BSO:Cr. Again this could be related to the donor activity of the P co-dopant, keeping the antisite centre in the diamagnetic Bi M 3+ state, but also the concentration of available bismuth antisite ions is strongly reduced by P doping in these crystals, as previously reported.…”
Section: A Epr Experimentsmentioning
confidence: 65%
“…First Ramaz et al [13] using magnetic circular dichroism demonstrated that Ru n+ substitute Bi-sites in pseudo-octahedron position under three valence states: Ru 4+ can accept holes or electrons to produce Ru 5+ or Ru 3+ , respectively due to it's amphotetic behavior. Further electron paramagnetic resonance direct detection proved that Ru doping results in (Bi 3+ Si + h) center already in the as-grown crystal and Ru introduces electron accepting levels close to the valence band (VB) [17]. Recently, photoinduced absorption study reveal an evidence of Ru-related high density of trap levels (positioned more shallow than the deep levels typical for sillenites), acting as acceptor centers for photoexcited electrons [18].…”
Section: Methodsmentioning
confidence: 99%